(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2014)
The ability to write and respond in a formal manner is an important skill in different areas. It has been seen that learners have problem with how to write and/or to respond in a formal manner. Being a quasi-experimental study, this study investigated the opportunities virtual instruction creates for the development and assessment of English responsive writing ability. The underlying premise was that virtual instruction, i.e., e-learning, can assist foreign language learners in the development of their general responsive writing ability. However, the role of instructional setting could not be so easily overlooked. So, the purpose of the present study was to recognize if there is any difference between EFL and ESL learners general responsive writing ability. In order to meet the objectives, 60 learners, divided into ESL and EFL groups, participated in this study. The ESL group consisted of 20 participants and 40 EFL learners were divided into two groups; one as the experimental group which received virtual instruction, while the other as the control group received class-based instruction. The study employed a process of exchanging emails in order to trace responsive writing ability development. Findings indicate that virtual instruction as far as the responsive writing ability was concerned, has an effective role in enhancing the learners written responses. Furthermore, these findings also show that the learners of the two EFL and ESL experimental groups significantly outperformed the EFL Control group, though the EFL experimental group outperformed both ESL and control groups. The findings also indicate that the EFL learners development depends on the researchers responsive written feedback.